واقع تطبيق مشروع البوابة الإلكترونية المدرسية - عزام عوض, فارس; عفونة, سائدة; عطير, ربيع (جامعة الوادي - University of Eloued, 2020)
الملخص: هدفت الدراسة التعرف إلى واقع تطبيق مشروع البوابة الإلكترونية المدرسية في المدارس الحكومية في مديريات محافظة جنين، وتكونت عينة الدراسة من (148) مدير ومديرة، و(352) معلم ومعلمة أي ما نسبته (11%) من مجتمع الدراسة، واستخدم الباحث الاستبانة كاداة للدراسة. وتوصلت الدراسة إلى: أن الدرجة الكلية لواقع تطبيق مشروع البوابة الإلكترونية كانت متوسطة، كما أظهرت عدم وجود فروق تعزى لمتغير الجنس، ومتغير العمر فقد كانت الفروق على المجال الثاني والخامس لصالح الفئة العمرية (31- 40)، والمؤهل العلمي فقد كانت الفروق للمجال الثاني لصالح حملة دبلوم فأعلى، والخبرة فقد كانت الفروق على المجال الرابع لصالح من لديهم خبرة أكثر من (6) أعوام، والدورات التدريبية فقد كانت الفروق على الدرجة الكلية والمجال الثاني لصالح الفئة التي حصلت على أكثر من (3) دورات، والوظيفة كانت الفروق على المجال الأول والثاني لصالح المدراء. وكانت اهم التوصيات، أن تقوم وزارة التربية والتعليم العالي بالإعلام والتوعية بأهمية البوابة الإلكترونية. Abstract: The study aimed to identify the reality of the implementation of the E-school project in the public schools in the directorates of Jenin Governorate. The sample of the study consisted of (148) principals and 352 teachers (11% of the study population). The researcher used the questionnaire as a research instrument. The study found that the overall score of the reality of the implementation of the E-school project was moderate. There were no significant differences due to the variable of gender. Differences in age in the second and fifth area were in favor of the age group (31-40). differences in qualifications in the second area were in favor of a diploma and above. Differences in experience in the fourth area were in favor of more than 6 years. Differences in training in the total score and the second area were in favor of those who attended more than three courses. Differences in the job in the first and second areas were in favor of principals. The study recommended that the Ministry of Education should raise awareness of the importance of the E-school.
مقال
Keywords: البوابة، الإلكترونية، المدارس الحكومية; E-school, public school